Personal Computer Security Threats in Bengaluru India - Kukkala, Varsha; Banshal , Sumit Kumar (International Journal of Information Systems and Technology, 2024)
India’s personal computer (PC) usage is increasing significantly every year and this increase poses a huge opportunity for security threats as many individuals may not have adequate knowledge about good security practices. The paper aims to study the state of PC security threats in Bangalore which is one of the major cities in South-Western India. We used statistical software to process and analyze the questionnaires we collected. The results of the study show that (i) PC ​​users implement good authentic passwords but this does not provide security for their devices, (ii) PC ​​owners do not update their anti-virus software and some PC protection software regularly which can create loopholes for malicious attackers (iii) PC ​​owners use many free subscription accounts and this can be a trigger for privacy threats.